2022
DOI: 10.31538/iijse.v5i2.2161
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Total Quality Management (TQM) on Quality Cost Efficiency and Managerial Performance and the Implications for Company Performance

Abstract: The study aimed to determine the effect of Total Quality Management (TQM) on quality cost efficiency and managerial performance and its implications on company performance. In the research, the researchers involved 100 companies in Indonesia. The analysis used is a structural approach to the Equation Model (SEM) assisted by the Smart PLS application. The results showed that there was a significant positive effect between total quality management, quality cost efficiency, managerial performance, and total manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies from many specialists emphasize the TQM concept by using or analyzing it in many fields or situations. Many studies reported positive relationship between TQM and organizational performance with different practices to be considered as the major practices affecting the successful implementation of TQM (Elvina, Anggraeni, Sasongko, & Erlandian, 2022). Based on the study (Androwis, Sweis, Tarhini, Moarefi, & Hosseini Amiri, 2018), it can be noticed that employees in the Jordanian construction chemicals companies believe that more efforts should be exerted on improving the above five practices so as to enhance the performance of their companies.…”
Section: Review Of Literaturementioning
confidence: 97%
“…Numerous studies from many specialists emphasize the TQM concept by using or analyzing it in many fields or situations. Many studies reported positive relationship between TQM and organizational performance with different practices to be considered as the major practices affecting the successful implementation of TQM (Elvina, Anggraeni, Sasongko, & Erlandian, 2022). Based on the study (Androwis, Sweis, Tarhini, Moarefi, & Hosseini Amiri, 2018), it can be noticed that employees in the Jordanian construction chemicals companies believe that more efforts should be exerted on improving the above five practices so as to enhance the performance of their companies.…”
Section: Review Of Literaturementioning
confidence: 97%